2022
DOI: 10.3389/fmars.2022.923093
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Variability of the East Sea Intermediate Water Thickness: Regime Shift of Intermediate Layer in the Mid-1990s

Abstract: The shipboard measurements over approximately 55 years in the southwestern part of the East Sea (Sea of Japan) demonstrate a remarkable basin-wide, interannual-interdecadal variability in the temperature-based thickness of the East Sea Intermediate Water (ESIW) whose temporal variability shows strong correlation with the density-based thickness (r = 0.97). Relevant to the long-term variability of the ESIW thickness, clear changes in horizonal and vertical features have been observed at the intermediate layer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…series of chlorophyll-a concentrations from the EJS over the period 2003-2020 and found that chlorophyll-a concentration increased in most of the EJS. Wind speed and direction, and SST, which are important physical parameters affecting the long-term trend in chlorophyll-a concentration, also showed characteristic trends and were related to Arctic Oscillation index variability (Park, 2022).…”
Section: Temporal Trendsmentioning
confidence: 94%
“…series of chlorophyll-a concentrations from the EJS over the period 2003-2020 and found that chlorophyll-a concentration increased in most of the EJS. Wind speed and direction, and SST, which are important physical parameters affecting the long-term trend in chlorophyll-a concentration, also showed characteristic trends and were related to Arctic Oscillation index variability (Park, 2022).…”
Section: Temporal Trendsmentioning
confidence: 94%
“…This facilitates effective ventilation in the East Sea, in response to even minor surface perturbations. The second driver is the frequent formation of cold and dense surface water associated with variations in the Arctic Oscillation (AO) (Cui & Senjyu, 2010; Nam et al., 2016; Park, 2022). These climate‐driven changes in ventilation intensity can either diminish or enhance the transfer of C ANTH ‐enriched surface water to the basin interior (Min & Warner, 2005; Park et al., 2006).…”
Section: Introductionmentioning
confidence: 99%